2011
DOI: 10.1186/1471-2164-12-438
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis and temperature-dependent transcriptome profiles of the rhizosphere originating strain Pseudomonas aeruginosa M18

Abstract: BackgroundOur previously published reports have described an effective biocontrol agent named Pseudomonas sp. M18 as its 16S rDNA sequence and several regulator genes share homologous sequences with those of P. aeruginosa, but there are several unusual phenotypic features. This study aims to explore its strain specific genomic features and gene expression patterns at different temperatures.ResultsThe complete M18 genome is composed of a single chromosome of 6,327,754 base pairs containing 5684 open reading fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 76 publications
3
53
0
Order By: Relevance
“…Considering core genome based phylogeny, the strain LESB58 hypervirulent for CF patients is the closest relative to the rhizosphere strain M18 [25]. However, dominant epidemic clones have been associated to CF.…”
Section: Pseudomonas Aeruginosa the Swiss Army Knifementioning
confidence: 99%
“…Considering core genome based phylogeny, the strain LESB58 hypervirulent for CF patients is the closest relative to the rhizosphere strain M18 [25]. However, dominant epidemic clones have been associated to CF.…”
Section: Pseudomonas Aeruginosa the Swiss Army Knifementioning
confidence: 99%
“…1 and 4), and most genomic differences are confined to accessory regions that account for less than 10 % of the ORFs present. Strain M18 was more susceptible than the virulent strain LESB58 to several antimicrobial agents applied against P. aeruginosa in clinical settings and was more readily cleared than LESB58 from the lungs in the acute mouse infection model (Wu et al 2011). Comparative transcriptome analyses of M18 and PAO1 grown at 28°C (''rhizosphere temperature'') and 37°C (''human temperature'') revealed that M18-induced more genes at 37°C than at 28°C and conversely, that more genes were induced in PAO1 at 28°C than at 37°C, consistent with gene mobilization in both strains to adapt to stresses associated with temperature-shifted growth (Wu et al 2012).…”
Section: Biological Control and Safetymentioning
confidence: 98%
“…For example, Wu et al (2011) identified the genomic differences between the MBCA P. aeruginosa M18 and certain P. aeruginosa strains, which are human pathogens. They underlined the genetic distance and the lack of genes involved in human pathogenicity in the MBCA strain, prerequisites for any plant protection product registration.…”
Section: Genome Sequencing Of Biocontrol Agentsmentioning
confidence: 99%
“…The MBCA transcriptome studies have been particularly useful in terms of providing a better understanding of how these MBCAs act and of the complex gene regulation sustaining the effect of the MBCA on the pathogenesis. More specifically the results highlighted genes involved in niche adaptation, competition for nutrients and space (Adomas et al 2006;Wu et al 2011), the complex interplay and synchronization of gene transcription needed for efficient mycoparasitism (Reithner et al 2011) and the more comprehensive understanding of the cell physiology sustaining mycoparasitism (Seidl et al 2009) or the kinetics of MBCA-pathogen interactions (Barret et al 2009a, b). The plant transcriptome studies have identified the plant defense pathways stimulated by the MBCA against the plant pathogen.…”
Section: Transcriptomic Studies Of Biocontrol Agentsmentioning
confidence: 99%